Care Utilization and Measures of the Subjective - Alexander Drost; Nadia Azib; Ali Azarpey; Philippe Dentino; Diego Tijerina; David Ring; Amin Razi (Chronic Stress)
Background In musculoskeletal health and care, visits, tests and treatments are often optional. There is some evidence that levels of utilization can be associated with subjective aspects of the illness, mindsets (thoughts and feelings about sensations) and stressful circumstances in particular. In a cross-sectional study of people seeking musculoskeletal specialty care, we addressed two questions: 1) Is there a difference in planned care utilization based on statistical groupings of measures of the subjective aspects of the illness? And 2) Are there any factors specifically associated with scheduling a return visit? Methods One hundred thirty-five patients seeking musculoskeletal specialty care completed measures of subjective patient factors including unhelpful thoughts and feelings of distress regarding symptoms, personal health agency, social health, and trust and experience with the clinician. Plans for a return visit, an injection, an imaging test, or referral to a physical therapist were documented. Cluster analysis was utilized to identify statistical groupings of scores on measures of subjective personal factors. Bivariate and logistic regression analyses evaluated factors associated with planned care utilization. Results We identified four statistical groupings of subjective factors through Cluster analysis: Group 1 had low trust, agency, and social health; Group 2 had low social health and high distress; Group 3 had healthy mindset and circumstances; and Group 4 had the highest social health and relatively healthy levels of the other subjective measures. Furthermore, no difference observed between statistical groups of the subjective regarding planned care utilization. Multivariable analysis revealed an association between scheduling a return visit and lower extremity clinicians (RC = 0.3; 95% CI 0.05 to 0.5; P-value, 0.02) but not with statistical groupings of measures of personal factors. Conclusion The finding that statistical groupings of patient personal factors were not associated with planned utilization of visits, tests, or treatments is inconsistent with other evidence linking mindsets actual utilization. A better understanding of sources of variation in planned and actual utilization is needed to help limit unwarranted variation and enhance effective use of resources.